PATHOGENECITY OF GROUPER SLEEPY DISEASE IRIDOVIRUS (GSDIV: Megalocytivirus, FAMILY Iridoviridae) TO CORAL TROUT GROUPER Plectrophomus leopardus - Ketut Mahardika; Ahmad Muzaki; Ketut Suwirya (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2009)
Grouper sleepy disease iridovirus (GSDIV), a member of the genus Megalocytivirus in the family Iridoviridae, has been known to cause large scale mortalities resulting in severe economic losses in grouper industries in south-east Asia including Indonesia. In this study, experimental infection of coral trout grouper Plectrophomus indicus with GSDIV was performed to evaluate the viral pathogenecity to this fish species. After virus exposure, the mortalities of coral trout grouper injected with primary and 10-1 dilution of spleen homogenates derived from tiger grouper Epinephelus fuscoguttatus were 100% and 90%, respectively. Histopathology revealed that moribund fish receiving GSDIV inoculum displayed massive formation of enlarged cells in the spleen and hematopoitic tissues. Under electron microscopy, the enlarged cells were observed as inclusion body bearing cells (IBCs) and necrotic cells allowing virus propagation within an intracytoplasmic virus assembly site (VAS). GSDIV virions were 167-200 nm in size. These findings confirmed that GSDIV has severe pathogenicity to coral trout grouper and IBCs as well as necrotic cells were determined to be the pathognomonic sign of megalocytivirus-infected coral trout grouper.